KARAKTERISTIK DAN POLA SEBARAN SEDIMEN PERAIRAN SELAT RUPAT BAGIAN TIMUR - Edy J Girsang; Rifardi Rifardi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
The study was conducted in June 2013 in the eastern waters of RupatStrait. The purpose of the study was to determine the depositional environmentand environmental changes along Rupat Straitbased on analysis of surfacesediment, suspended sediment concentration, and sediment accumulation value.The method used was survey method. Location of the studywas divided into 15sampling points based onthe pattern oftidal currents and source materials into thewater. The results showed that the study area was dominated by fine s andsediments with as and sediment type. The average concentration of suspendedsolids in coastal waters of Sumatra washigherthan that of the Rupat. The waters ofthe eastern part of the Rupat Strait received sediment from the coastal erosion andsupply of material from the two major rivers; i.e. Dumai River and Masjid River.Characteristics and distribution patterns in marine sediments were influenced bythe character of the sea bottom, the pattern of tidal currents and waves .Keywords : Charackteristics of Sediments, Surface Sediment, Rupat Strait.